1953
DOI: 10.1084/jem.97.2.297
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Bacteremia in Experimental Pneumococcal Pneumonia in the Dog

Abstract: In the preceding study of the relationship of the natural pneumococcidalpromoting activity of the serum to bacteremia in dogs with experimental pneumococcal pneumonia (1), it was found that the blood of non-bacteremic dogs retains its natural humoral immunity with a remarkable degree of constancy. The occurrence of bacteremia was followed by wide individual variations in the concentration of these antipneumococcal properties, ranging from complete disappearance in the presence of relatively few circulating pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1955
1955
1975
1975

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Many years ago Wright showed that the blood stream clearance of a particular strain of pneumococcus could be directly related to the bactericidal power of the peripheral blood in vitro (14). This finding has been confirmed by others (8).…”
Section: Participation Of Circulating Leucocytes In Clearancementioning
confidence: 78%
See 1 more Smart Citation
“…Many years ago Wright showed that the blood stream clearance of a particular strain of pneumococcus could be directly related to the bactericidal power of the peripheral blood in vitro (14). This finding has been confirmed by others (8).…”
Section: Participation Of Circulating Leucocytes In Clearancementioning
confidence: 78%
“…It is generally agreed that the histiocytic cells of the vascular and lymphatic endothelium, characterized by Aschoff (4) by their ability to sequester vital dyes and particulate substances, are also responsible for the trapping of circulating microorganisms (5). The cells of the reticulo-endothelial system which appear most active in dye studies, the Kupffer cells lining liver capillaries, and the phagocytic cells in splenic sinuses appear to be the most important trapping sites in the early clearance of bacteria, although it is probable that the bone marrow, lymph node sinusoids, and other fixed phagocytic cell depots also participate (6)(7)(8)(9)(10)(11)(12)(13)(14). Quantitative studies on the organ distribution of intravenously administered microorganisms indicate that the liver collects the majority of bacteria when clearance is rapid.…”
Section: Splanchnic Tissuesmentioning
confidence: 99%
“…The rate of clearance might abruptly decline or cease if raiculoendothelial removal mechanisms were fully saturated.--There is abundant evidence to suggest that this is not the case. Clearing mechanisms have been shown to operate effectively after secondary injections of bacteria, or in the presence of overwhelming bacteriemia (6,11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic trapping of E. coli is less effective than that observed with staphylococci (6,10). Studies on pneumococcal bacteriemia in rabbits and dogs have suggested that clearance of this microorganism depends upon circulating leukocytes rather than the splanchnic tissues (14,15). The studies of Wood and his associates have dearly documented the intravascular phagocytosis of this microorganism during pneumococcal bacteriemia (16).…”
Section: Discussionmentioning
confidence: 99%